High-Tech Industry in the EU: Policy, Economy, Statistics - Salikhova, O. B. (Statistics of Ukraine, 2024)
The analysis of the legal framework supporting the European Union’s decisions on the EU industrial sector, particularly high-tech manufacturing, shows that the European Commission maintains a long-standing commitment to prioritizing technological development in industries. To enhance their potential and competitive advantages, mechanisms of industrial, scientific-technological, and innovation policy are primarily employed. At the same time, research results show the growing trade deficit EU high-tech trade. The aim of the article is to deepen understanding on the policy and economic dimensions of high-tech activity, as well as to statistical estimates of production and international trade flows of high-tech goods in EU between 2008 and 2023. The economic-statistical analysis revealed that, since the early 2000s, the EU has gradually increased its trade deficit in high-tech goods with China. In 2009, the negative balance was €43.1 billion, rising to €73.1 billion by 2019; in 2022, the trade deficit with China reached a historic high of €129.6 billion; by the end of 2023, it was €105.5 billion. Countries such as Thailand, South Korea, Malaysia, Taiwan, and Vietnam have significantly increased their exports of high-tech goods to the EU since 2019, contributing to a growing negative balance. Before the pandemic in 2019, imports from Asian countries of high-tech goods in the groups of Electronics & Telecommunications and Computers and office machines grew at the highest rates. In the category of Electronics & Telecommunications, imports from China increased from €63,013.9 million to €89,228.1 million from 2019 to 2023; imports from Taiwan – from €3,644.7 million to €16,489.4 million; and imports from Vietnam – from €110.2 million to €14,053.8 million. In the category of Computers and office machines, imports from China increased from €40,177.4 million to €42,752.0 million; imports from Taiwan – from €802.6 million to €9,917.6 million; and imports from Vietnam – from €21.1 million to €2,787.2 million. This led to a significant trade deficit for the EU in high-tech goods from these countries. The work substantiates that the EU leadership has adopted new political documents, which prioritize reducing strategic external dependency on imports and implementing measures to enhance their effectiveness. It should serve as benchmarks for developing policies for the growth of high-tech industries in Ukraine amid wartime conditions and post-war economic recovery.